INVESTIGATION ON TENSILE STRENGTH OF DOWEL JOINT IN PARTICLEBOARD FASTENING - Habib Nori (Regional Information Center for Science and Technology (RICeST), 2005)
Poplar trees are classified as a fast growth trees and because of short rotation period, and suitable technical properties, are considered by pulp and paper making industries. In this study, physical and anatomical properties and pulp and paper of three colons of poplar trees, populous Alba. L. colon 44.9, populous deltoids 69.55, and populous euramerican are investigated. The average fiber length of these three colons were 0.854, 1.148, 1.08 mm. respectively and their average dry specific gravity were 0.386, 0461, and 0.341 g/cm3, and also their average cellulose content were 50.5, 51.5, and 49.5 percent.For Kraft process cooking of the mentioned colons, three cooking time, 1, 2, and 3 hours, 17°C cooking heat, 25% sulfidity, and active alkali at 3 levels, 15, 17.5, and 20% were used. The results show that p. alba, colon 44.9, and p. deltoids colon 69.55 with using 20% A.A and 3 hours cooking time have 53% yield and 18 kappa number.